Febrile Seizure Duration and Development - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Members of the FEBSTAT multicenter Study Team assessed the distribution of febrile seizure (FS) duration in a cohort of 158 children with a first FS, and determined the association between FS duration and behavior and development.